Rights of the accused before the International Criminal Court during the investigation phase - Yazeed Hamdan Al-Bahith (International Journal of Law Research and Studies, 2025)
This research aims to examine the rights of the accused before the International Criminal Court during the investigation stage, which is considered the most sensitive and influential phase in the course of international criminal proceedings. The study explores the establishment of the International Criminal Court and the mechanisms for initiating investigations, whether through referrals by State Parties, the UN Security Council, or the Prosecutor’s proprio motu powers. It further highlights the key guarantees afforded to the accused, including the right against self-incrimination, the prohibition of coercion and torture, the right to legal assistance and interpretation, the right to access investigation materials, the documentation of investigative procedures, and the right to remain silent. These safeguards play a fundamental role in ensuring fair trial standards and protecting human dignity. The research concludes that upholding these rights is essential for achieving international justice, despite the existence of certain gaps that call for clearer and more comprehensive legislative regulation within the Rome Statute and its procedural framework.